Sovereign Debt Restructuring and Debt Sustainability : An Analysis of Recent Cross-Country Experience - Finger, Harald; Mecagni, Mauro (Washington, D.C. : International Monetary Fund, 2007)
Restoring a country's debt to a sustainable path after a sovereign debt restructuring is key to ensuring a credible and durable exit from the crisis. In recent years, a number of countries have restructured their sovereign liabilities, either following a default, or preemptively, to avoid a default. This Occasional Paper takes stock of the experiences of some of these countries--Argentina, the Dominican Republic, Ecuador, Moldova, Pakistan, Russia, Ukraine, and Uruguay--with debt-restructuring operations, with a view to assessing the outcomes and whether debt sustainability has been restored. The emphasis of the study is on sovereign debt owed to private creditors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet